Indoxyl Sulfate Induces Apoptosis and Hypertrophy in Human Kidney Proximal Tubular Cells. (June 2018) - Ellis, Robert J.; Small, David M.; Ng, Keng Lim; Vesey, David A.; Vitetta, Luis; Francis, Ross S.; Gobe, Glenda C.; Morais, Christudas
Indoxyl sulfate (IS) is a protein-bound uremic toxin that accumulates in patients with declining kidney function. Although generally thought of as a consequence of declining kidney function, emerging evidence demonstrates direct cytotoxic role of IS on endothelial cells and cardiomyocytes, largely through the expression of pro-inflammatory and pro-fibrotic factors. The direct toxicity of IS on human kidney proximal tubular epithelial cells (PTECs) remains a matter of debate. The current study explored the effect of IS on primary cultures of human PTECs and HK-2, an immortalized human PTEC line. Pathologically relevant concentrations of IS induced apoptosis and increased the expression of the proapoptotic molecule Bax in both cell types. IS impaired mitochondrial metabolic activity and induced cellular hypertrophy. Furthermore, statistically significant upregulation of pro-fibrotic (transforming growth factor-β, fibronectin) and pro-inflammatory molecules (interleukin-6, interleukin-8, and tumor necrosis factor-α) in response to IS was observed. Albumin had no influence on the toxicity of IS. The results of this study suggest that IS directly induced a pro-inflammatory and pro-fibrotic phenotype in proximal tubular cells. In light of the associated apoptosis, hypertrophy, and metabolic dysfunction, this study demonstrates that IS may play a role in the progression of chronic kidney disease.